THE ECONOMIC IMPACT OF THE DEVELOPMENT OF THE TANGKAHAN ECOTOURISM IN NAMO SIALANG VILLAGE, LANGKAT REGENCY - Louise, Gabriele; Marsongko, Eka Pramita; Odang Permana (International Journal of Sustainable Competitiveness on Tourism, 2022)
Ecotourism is one of the sustainable alternative tourism developed in Indonesia, one of which is the Tangkahan Ecotourism destination. Namo Sialang Village is one of the villages directly connected to Tangkahan Ecotourism. This ecotourism destination has a history of illegal logging to the thoughts and behavior of the surrounding community for sustainable changes in Tangkahan's nature. The development of Tangkahan Ecotourism certainly has an impact on the people of Namo Sialang Village. According to UNWTO, one aspect of impact is socioeconomic sustainability. This study uses sustainable socioeconomic indicators issued by the Global Sustainable Tourism Council (GSTC) Criteria assessment agency on the consideration of the character of Namo Sialang Village as an area around the Tangkahan Ecotourism conservation area. Indicators of socioeconomic sustainability are used to see the benefits of the local economy and the natural environment. The subjects of this research are the people of Namo Sialang Village, to be precise in Kwala Gemoh and Kwala Buluh Hamlets. The purpose of this study was to determine the impact of the development of Tangkahan Ecotourism on the economy of the people of Namo Sialang Village. The research method used is a quantitative approach with quantitative analysis tools using a statistical package for the social science (SPSS) tools. The results of this study indicate the impact of tourism development in Tangkahan which has been carried out following the principles of ecotourism development. Where the percentage of positive responses from the community, which is 70%, feels the benefits of the local economy, is involved in community participation, and receives support from the development of Tangkahan Ecotourism